'An indefatigable intermediary': Harold Woodbury Parsons (1882–1967) and the formation of the European collections at the Cleveland Museum of Art, part 1. (11th March 2020) - Rowlands, Eliot W
Abstract: At a time when museum curatorship in America was in its infancy, Harold Woodbury Parsons (1882–1967) scouted and negotiated for outstanding works of art for the cash-rich Cleveland Museum of Art, which opened to the public in 1916. As its European representative (1925–41), he acquired such masterworks as the Stroganoff Ivory, El Greco's Holy Family with St Mary Magdalen, and the Warren tondo by Filippino Lippi, all during the late 1920s. During a lifetime's work in the art market, in which he worked for private collectors and other museums, this was his most important achievement. What he acquired for the Cleveland Museum is vividly recounted in the art agent's correspondence, until now, almost entirely unpublished. After moving to Rome in 1910, Parsons first served as 'an indefatigable intermediary' in the world market for antiquities. Later, with the blessing of Edward Waldo Forbes and Paul J. Sachs – director and assistant director, respectively, of Harvard's Fogg Art Museum – and with a host of European contacts, he was able to 'gun for' art for an ever expanding number of clients.